The Impact of Digital Technology on Environmental Quality: Empirical Evidence from Indonesia - Kartiasih, Fitri; Rosanti, Hanifah Putri; Miswa, Sabrina Do; Hakim, Arif Rahman (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This research investigates how digital technologies influence environmental quality in Indonesia.Research Objectives: This study examines the impact of digital technologies and socioeconomic variables on environmental quality in Indonesia.Research Methods: This study employs the System-Generalized Method of Moments (GMM) approach and analyzes data from 2013 to 2023. Key variables include digital technology, gross regional domestic product (GRDP), foreign direct investment (FDI), and mean years of schooling.Empirical Results: Computer ownership negatively impacts environmental quality due to higher energy consumption and e-waste. In contrast, GRDP improves environmental quality as wealthier regions invest in green infrastructure and stricter policies. FDI has a harmful effect, supporting the ‘pollution haven’ hypothesis of resource exploitation and unsustainable practices. Education fosters environmental awareness, though its influence is still limited.Implications: Digital technologies can enhance environmental quality, requiring strategic planning and continuous innovation by central and local governments.JEL Classification: O11, O13, Q56How to Cite:Kartiasih, F., Rosanti, H.P., Miswa, S.D., & Hakim, A.R. (2025). The Impact of Digital Techonologies on Environmental Quality: Empirical Evidence from Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 77-92. https://doi.org/10.15408/sjie.v14i2.44874.